Use of an injection of aripiprazole given once every 2 months (Abilify Asimtufii) in people with bipolar I disorder: a Plain Language Summary of Publication - Roger S. McIntyre; Pedro Such; Murat Yildirim; Jessica Madera-McDonough; Na Jin; Suzanne Watkin; Zhen Zhang; Frank Larsen; Matthew Harlin (SAGE Publishing, 2024)
The purpose of this summary is to explain key findings from a study that included people with bipolar I disorder, as described in two separate articles (see the 'Further Information' section for more details). The study compared a new formulation of aripiprazole, given as an injection once every 2 months, with a once‑monthly injection of aripiprazole.